COMMUNICATION PATTERNS OF RELIGIOUS PLURALITY COMMUNITIES IN SUMBERMULYO VILLAGE PESANGGARAN BANYUWANGI - Turmudi, Imam; Sorayya, Dharma (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2024)
ABSTRACT Sumbermulyo Village is a replica of Indonesia in terms of multiculturalism. Sumbermulyo is a village located in the southern Banyuwangi region, precisely in Pesanggaran District, Banyuwangi Regency. This research aims to find out the Communication Patterns of Religious Plurality Communities in Sumbermulyo Pesanggaran Banyuwangi Village and Community Efforts to Resolve Conflicts with Socio-religious Backgrounds in Sumbermulyo Village, Pesanggaran District, Banyuwangi Regency. The research method in this study uses Qualitative used to answer research problems in the form of narrative related data obtained from various research techniques through interviews, observation, and documentation. The results of this research are the efforts of the Sumbermulyo community so that this diversity continues to run dynamically and harmoniously, some interfaith leaders respect different religions, such as attending invitations, attending celebrations and other celebrations. And also always work together in building places of worship despite religious differences. ABSTRAK Desa Sumbermulyo merupakan replika Indonesia dalam hal multikultural. Sumbermulyo merupakan sebuah desa yang terletak di wilayah Banyuwangi selatan tepatnya di Kecamatan Pesanggaran Kabupaten Banyuwangi. Penelitian ini bertujuan untuk mengetahui Pola Komunikasi Masyarakat Pluralitas Agama Di Desa Sumbermulyo Pesanggaran Banyuwangi serta Upaya Masyarakat Menyelesaikan Konflik Yang Berlatar Belakang Sosial Keagamaan di Desa Sumbermulyo Kecamatan Pesanggaran Kabupaten Banyuwangi Metode penelitian dalam penelitian ini menggunakan Kualitatif digunakan menjawab permasalahan penelitian berupa data terkait naratif yang diperoleh dari berbagai teknik penelitian melalui wawancara, observasi, dan dokumentasi. Hasil Peneltian ini yaitu Upaya masyarakat Sumbermulyo supaya keberagaman ini tetap berjalan dinamisdan harmonis maka beberapa tokoh antar agama melakukan penghormatan terhadap beda agama, semisal menghadiri undangan, menghadiri selametan dan hajatan lainnya. Serta juga selalu gotong royong dalam membangun tempat ibadah meskipun memiliki perbedaan agama